Disease stress in Poultry; Letter to editor - Ayesha Muazzam (Information Technology and Science (ITScience), 2022)
I am writing this letter to you in order to bring light toward the special issue of poultry production in Pakistan. There are several diseases in poultry which causing stress in poultry production. Some are viral diseases which don’t have treatment [1, 2, 3, 4, 5]. Only vaccination and biosecurity measures can prevent disease. There are some viral diseases which are effecting poultry badly, Newcastle Disease, Infectious Bronchitis, Marek’s Disease, Infectious Chicken Anemia, and Infectious Bursal Disease. Some are bacterial diseases which can be treated through antibiotics [6, 7, 8, 9]. There are some bacterial diseases which are effecting poultry badly, Infectious Coryza, MG, Salmonella diseases are some major bacterial disease. There are some Protozoal diseases which are effecting poultry production and these can be treated through anti-protozoal drugs.